FlbZIP12 gene enhances drought tolerance via modulating flavonoid biosynthesis in Fagopyrum leptopodum - Wang, Anhu; Liu, Yu; Li, Qiujie; Li, Xiaoyi; Zhang, Xinrong; Kong, Jiao; Liu, Zhibing; Yang, Yi; Wang, Jianmei (Frontiers in Plant Science, 2023)
Karst lands provide a poor substrate to support plant growth, as they are low in nutrients and water content. Common buckwheat (Fagopyrum esculentum) is becoming a popular crop for its gluten-free grains and their high levels of phenolic compounds, but buckwheat yields are affected by high water requirements during grain filling. Here, we describe a wild population of drought-tolerant Fagopyrum leptopodum and its potential for enhancing drought tolerance in cultivated buckwheat. We determined that the expression of a gene encoding a Basic leucine zipper (bZIP) transcription factor, FlbZIP12, from F. leptopodum is induced by abiotic stresses, including treatment with the phytohormone abscisic acid, salt, and polyethylene glycol. In addition, we show that overexpressing FlbZIP12 in Tartary buckwheat (Fagopyrum tataricum) root hairs promoted drought tolerance by increasing the activities of the enzymes superoxide dismutase and catalase, decreasing malondialdehyde content, and upregulating the expression of stress-related genes. Notably, FlbZIP12 overexpression induced the expression of key genes involved in flavonoid biosynthesis. We also determined that FlbZIP12 interacts with protein kinases from the FlSnRK2 family in vitro and in vivo. Taken together, our results provide a theoretical basis for improving drought tolerance in buckwheat via modulating the expression of FlbZIP12 and flavonoid contents.